2017
DOI: 10.1038/ncomms15875
|View full text |Cite|
|
Sign up to set email alerts
|

Skillful prediction of northern climate provided by the ocean

Abstract: It is commonly understood that a potential for skillful climate prediction resides in the ocean. It nevertheless remains unresolved to what extent variable ocean heat is imprinted on the atmosphere to realize its predictive potential over land. Here we assess from observations whether anomalous heat in the Gulf Stream's northern extension provides predictability of northwestern European and Arctic climate. We show that variations in ocean temperature in the high latitude North Atlantic and Nordic Seas are refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
82
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 107 publications
(89 citation statements)
references
References 72 publications
(164 reference statements)
7
82
0
Order By: Relevance
“…Variability on decadal time scales of temperature and salinity associated with the warm Atlantic water pathway is of great scientific interest, as anomalies of such properties can have profound impact on the ocean climate along the pathway, and potentially on northwestern European climate (e.g., Collins and Sinha 2003;Årthun et al 2017). In this study, our main purpose is to investigate to what extent a forced global ocean-sea ice model is able to represent known characteristics of the Atlantic water pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variability on decadal time scales of temperature and salinity associated with the warm Atlantic water pathway is of great scientific interest, as anomalies of such properties can have profound impact on the ocean climate along the pathway, and potentially on northwestern European climate (e.g., Collins and Sinha 2003;Årthun et al 2017). In this study, our main purpose is to investigate to what extent a forced global ocean-sea ice model is able to represent known characteristics of the Atlantic water pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The poleward propagation of thermohaline anomalies is considered to be a main source of climate predictability (Årthun and Eldevik 2016;Årthun et al 2017;Yeager and Robson 2017). The purpose of this study is twofold: (1) We investigate how properties associated with the warm Atlantic water is expressed along its pathway, using observational data and a forced global ocean-sea ice model.…”
Section: Discussionmentioning
confidence: 99%
“…Atmospheric forcing may be the biggest contributor to the sea ice loss (Serreze et al, ), but ocean heat storage and transport play an important role in certain regions (Carmack et al, ; Perovich & Richter‐Menge, ; Polyakov et al, ). For example, the decline and variability in winter sea ice cover north of Svalbard and in the Barents and Kara Seas is linked to an increased and warmer inflow of Atlantic Water (AW; Årthun et al, , ; Barton et al, ; Li et al, ; Onarheim et al, , , ). The Barents Sea experiences the fastest surface warming in the Arctic (Screen & Simmonds, ), and a recent study by Lind et al () found that the northern Barents Sea has transitioned from a cold Arctic to a warm Atlantic‐dominated regime.…”
Section: Introductionmentioning
confidence: 99%
“…Ocean heat content variability plays an important role in our climate system. In the Arctic‐Atlantic region, ocean heat anomalies have been shown to affect sea ice (e.g., Årthun et al, ; Yeager et al, ), marine ecosystems (Hátún et al, ), and potentially also continental climate (Årthun et al, ). There is, however, at present neither consensus nor any complete understanding of the mechanisms causing and maintaining such heat anomalies.…”
Section: Introductionmentioning
confidence: 99%